The E-Book in the Theory of Rushdi Ahmed Thu'aimah: A Comparative Study between Arabic Online and Modern Standard Arabic - Ledianto, Fajar; Thaifur, Ahmad Nuruddin; Rufaiqoh, Elok; Sodik, Achmad Ja’far (Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2024)
Arabic language learning will only develop if the value of the book's content and books are one of the most modern educational materials in this era. This study aims to determine electronic books according to Rushdi Ahmad Tuaimah's theory: Comparative Study of the Books Arabic Online and Modern Standard Arabic. The research methodology in this study used a descriptive library approach, and the type of research data was words and sentences in the book. The data sources were the books Arabic Online and Modern Standard Arabic. The data collection methods used for the study were reading, classification, and analysis. From the analysis of this book based on Rushdi Ahmad Tuaimah's perspective, what can be known is 1) The book